Light at night-A new challenge to cardiovascular health - Memon, Midori; Ali, Khadija (Journal of the Pakistan Medical Association, 2023)
Respected Madam, As Pakistan progresses to its potential in terms of economic growth and infrastructure, the light pollution in our country has increased more than ever. According to the data, from 2012-2013 to 2018-2019, there has been a 23.4% increase in light pollution in Lahore.1 Light intensity continues to increase, especially at night, with many falling asleep with the lights or the television on. The concerning fact about this is that emerging studies suggest that glowing at night during sleep harms cardiovascular health. Cardiovascular diseases are the second leading cause of death in Pakistan, and this new addition to the risk factors is very alarming.2 In a recent 2022 study by Minjee et al, risk factors for cardiovascular diseases were found to be associated with light at night(LAN) during sleep in older age.3 The LAN group was significantly more likely to have obesity (41% vs 27%), diabetes (18% vs. 9.8%), and hypertension (73% vs 59%) compared to the No-LAN group.3 Furthermore, in a 2019 study by Yong-Moon et al, it was found that women having any artificial light at night exposure while sleeping was positively associated with a higher prevalence of obesity at baseline.4 As the usage of electronics and artificial light at night becomes more common, we must be well informed about the potential side effects they can bring to our well-being, especially in Pakistan, where we are already overburdened with cardiovascular disease. Proper awareness must be given to our population, and more studies should be done in our country so that it can be catered to our demographics. Since light pollution is an unavoidable consequence of economic development, we must find ways to limit its intensity at night individually and as a society. The sooner we act on the risk factor, the more we can prevent cardiovascular disease incidence from progressing.